Synthesis, Characterization, and Photocatalytic Activity of Cu-Doped MgO Nanoparticles on Degradation of Methyl Orange (MO) - Gebreaneniya, Mebrihit Fissaha; Berhe, Goitom Gebreyohannes; Teklu, Tesfamariam (Advances in Materials Science and Engineering, 2024)
The purpose of this study is to synthesize Cu-doped MgO nanoparticles and test the performance of photocatalytic degradation of methyl orange (MO). Mg(NO3)2, CuCl2, NaOH, and fresh Calotropis procera leaf extract were used as precursors. The prepared nanoparticles were characterized by using FT-IR, XRD, SEM, and UV-Vis spectrometer to study the functional group, crystal structure, surface morphology, and absorption edge, respectively. The wide band above 3000 cm−1 from the FT-IR spectrum corresponds to the stretching vibrations of flavonoids and phenolic compounds of Calotropis procera leaf extract. Furthermore, the Mg-O bonding of undoped MgO and Cu-doped MgO NPs is represented by new peaks which appeared at 831 and 835 cm−1, respectively. The crystal size of undoped MgO and Cu-doped MgO nanoparticles is 13.04 nm and 12.08 nm, respectively. The SEM microstructure of pure MgO showed higher agglomeration than the Cu-doped MgO nanoparticles. The degradation efficiency of the Cu-doped MgO NPs was compared with that of the MgO NPs, and the photocatalytic activity of these NPs was evaluated using the photocatalytic degradation rates of MO dye. Cu-doped MgO NPs showed higher degradation efficiency than pure MgO NPs. The insertion of Cu in the MgO structure improved the photocatalytic efficiency of the MgO NPs under optimal conditions. Therefore, Cu-doped MgO exhibits high photocatalytic activity compared with undoped MgO nanoparticles under sunlight irradiation.